2013
DOI: 10.1097/hcr.0000000000000019
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Ventilation Improves the Cardiovascular Response and Fatigability During Resistance Exercise in Patients With Heart Failure

Abstract: Bi-level positive airway pressure ventilation significantly improved the cardiovascular response and fatigability during resistance exercise in patients with heart failure. These results suggest that use of BV during exercise training may be beneficial in this population with chronic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…These findings suggest that exercise tolerance may be improved by manipulating intrathoracic pressure during exercise in patients with HFrEF. Accordingly, a less negative intrathoracic pressure resulted in marked improvement in heart rate, blood pressure, and performance during resistance exercise in patients with ischemic heart failure (28). In addition to its effect on preload and afterload, it must be considered that inspiratory unloading, via reducing the Wb and Pb, may improve exercise intolerance by attenuating the competition for cardiac output between respiratory and locomotor muscles.…”
Section: Respiratory Modulation Of Left Ventricular Function In the Failing Heartmentioning
confidence: 99%
“…These findings suggest that exercise tolerance may be improved by manipulating intrathoracic pressure during exercise in patients with HFrEF. Accordingly, a less negative intrathoracic pressure resulted in marked improvement in heart rate, blood pressure, and performance during resistance exercise in patients with ischemic heart failure (28). In addition to its effect on preload and afterload, it must be considered that inspiratory unloading, via reducing the Wb and Pb, may improve exercise intolerance by attenuating the competition for cardiac output between respiratory and locomotor muscles.…”
Section: Respiratory Modulation Of Left Ventricular Function In the Failing Heartmentioning
confidence: 99%
“…Furthermore, with respiratory muscle unloading, oxygen supply and demand are balanced, benefiting HF patients during high intensity exercise. 6 In addition, a meta-analysis showed that PAP application before the six-minute walk test in HF patients increased the walking distance. 7 …”
Section: To the Editormentioning
confidence: 99%